2021
DOI: 10.1177/2050313x211034683
|View full text |Cite
|
Sign up to set email alerts
|

An uncommon cause of soft tissue and knee infection after penetrating injury in a non-immunocompromised adolescent male

Abstract: Non-cholerae Vibrio species and Shewanella species are organisms that rarely infect humans. Symptoms can range from gastroenteritis to wound infections to septicemia. In addition, these infections can lead to multiple poor outcomes ranging from amputations to death. We present a case of an 11-year-old male with prepatellar bursitis of the right knee due to Vibrio parahaemolyticus and Shewanella algae following an open wound in the Gulf of Mexico complicated by retained oyster shell fragments. He completely rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In the past several decades, some marine-cultured animals including Lates calcarifer, Sparus aurata, Dicentrarchus labrax, Litopenaeus vannamei, Marsupenaeus japonicas, and Crassostrea gigas sufered serious production losses due to infection by V. alginolyticus [2][3][4][5][6][7]. It has been reported that V. alginolyticus also infected humans and caused gastroenteritis, wound infections, and septicemia and even amputations and death [8]. Due to the harmful efect caused by V. alginolyticus, farmers had to combat the disease with some treatment ways, such as antibiotics, green water technique, topical disinfectants, medicinal plants, bacteriophage, probiotics, and vaccines [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the past several decades, some marine-cultured animals including Lates calcarifer, Sparus aurata, Dicentrarchus labrax, Litopenaeus vannamei, Marsupenaeus japonicas, and Crassostrea gigas sufered serious production losses due to infection by V. alginolyticus [2][3][4][5][6][7]. It has been reported that V. alginolyticus also infected humans and caused gastroenteritis, wound infections, and septicemia and even amputations and death [8]. Due to the harmful efect caused by V. alginolyticus, farmers had to combat the disease with some treatment ways, such as antibiotics, green water technique, topical disinfectants, medicinal plants, bacteriophage, probiotics, and vaccines [9].…”
Section: Introductionmentioning
confidence: 99%